Récits et expériences du paysage urbain historique de Porto, ville inscrite au patrimoine mondial de l’humanité - Ana Rita Albuquerque (Projets de Paysage)
This article examines how the Historic Urban Landscape (HUL) approach (Unesco, 2011) focusing on heritage values contributes to the heritagization of “invisible” categories (Barthelemy and Istasse, 2022; Zamant, 2019) of which only “traces” remain (Veschambre, 2008). The aim is to understand the transition towards a heritage that integrates alterity in Porto, Portugal, through the example of Calçada das Carquejeiras, a place situated on the edge of the Unesco World Heritage site. Based on the historic urban landscape approach, the analysis focuses on three key concepts: narrative, co-presence and personal experience. This methodology contributes to a critical analysis of the process of the enhancement of a landscape heritage by a qualitative study combining semi-structured interviews, photographic analysis, press reviews, guided tours and institutional information in Porto. This article highlights the fact that in the heritagization of the ‘invisible’ categories of the urban landscape the feedback of the local population requires taking into account what the population says, the engagement of associations and institutional perspectives. It also highlights the fact that the multiplication of categories does not systematically lead to a greater inclusion of heritage. For this to happen, there is a need to promote mediation and varied and innovative methods for collecting data on the values of heritage landscapes. Approaches aimed at highlighting these heritages could then influence the evolution of normative frameworks at local and/or national level. There has been a notable shift towards more holistic approaches to the landscape, as in the case of the recognition of the history of the Carquejeiras and the adoption of the PUH approach in Porto.